Foaming Agents Affect the Physicochemical and Antioxidants in Red Dragon Fruit Powder Drinks from Foam Mat Drying - Hamad, Alwani; Mulyadi, Abdul Haris; Yulianti , Henti; Hartanti, Dwi; Naveed, Mubshair (Journal of Applied Science, Engineering, Technology, and Education, 2024)
This study investigated the effect of foaming agent type and concentration on foam characteristics during foam mat drying and the physicochemical and antioxidant properties of red dragon fruit powdered drink. Foaming agents, including soy lecithin, fresh egg whites, egg white powder, and whey protein concentrate, were tested at different concentrations (5%, 10%, and 20%). Results showed that soy lecithin produced the most stable foam, effectively preserving bioactive compounds such as phenolics and flavonoids, which contributed to higher antioxidant activity (measured by DPPH and FRAP methods). Whey protein concentrate and fresh egg whites enhanced foam overrun and moisture retention, leading to powders with lower moisture content and higher solubility. The optimal concentration of foaming agent was 10%, which resulted in the best foam stability, antioxidant preservation, and overall product quality. This study highlights the importance of selecting appropriate foaming agents and concentrations to improve the quality and antioxidant properties of red dragon fruit powdered drinks for food applications.